A Rare Case of Renal Infarct due to Noncompaction Cardiomyopathy: A Case Report and Literature Review. (28th February 2016) - Wats, Karan; Chen, On; Uppal, Nupur Nippun; Batul, Syeda Atiqa; Moskovits, Norbert; Shetty, Vijay; Shani, Jacob
Abstract : Left ventricular noncompaction cardiomyopathy is a rare myocardial disorder which results from failure of left ventricle to compact in embryogenesis. We present a case of a 53-year-old female who came because of abdominal pain and was found to have renal infarct secondary to noncompaction cardiomyopathy.